Evaluation of Haematococcus pluvialis concentrates as complete fish oil replacements and partial fishmeal substitutes in black tiger shrimp (Penaeus monodon) - Husniina, Azath Nur; Lee, Po Tsang; Xu, Qiyou; Chong, Chou Min; Karim, Murni; de Cruz, Clement R. (Taylor and Francis, 2026)
The dependence on fishmeal and fish oil in aquafeeds poses challenges to the long-term sustainability of aquaculture due to the pressure on limited marine resources. This study evaluated the potential of the microalga Haematococcus pluvialis (HP) as a partial substitute for fishmeal and a complete replacement for fish oil in the diet of black tiger shrimp (Penaeus monodon). Post-larvae (PL22) were reared for 56 days in a recirculating aquaculture system and fed five diets containing 0%, 8%, 12%, 16%, or 20% HP. Shrimp fed 12% HP showed significantly higher weight gain (1191.51%), daily weight gain (0.31 g day−1), and specific growth rate (4.56% day−1) compared with other dietary treatments (p <.05). Feed conversion ratio (1.09) and feed efficiency ratio (0.93) improved at 12% and 20% inclusion levels, respectively. Survival exceeded 95% at both levels, indicating that HP can effectively replace fish oil and partially replace fishmeal in shrimp feed.